PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PIXY DI PT. MANDOM INDONESIA Tbk. CABANG MEDAN - Fahmi D, Aswin; Aseandi, Riski (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This study aims to determine how much influence the level of compensation has on the performance of Pixy employees at PT. Mandom Indonesia Tbk. Medan Branch and to find out how much the level of motivation influences the performance of Pixy employees at PT. Mandom Indonesia Tbk. Medan Branch. This research uses quantitative research methods. The results of the research conducted show that the analysis obtained a t-count compensation value (X1) of 2,321 which is greater than the t-table of 1.66600 with a significance probability value of 0.001 <0.05, so that compensation has a positive and significant effect on employee performance PT. Mandom Indonesia Tbk Medan Branch. Based on the results of the analysis, the obtained t-count motivational value (X2) is 3.824 which is greater than the t-table of 1.66600 with a significance probability value of 0.000 <0.05, so that motivation has a positive and significant effect on the performance of employees of PT. Mandom Indonesia Tbk Medan Branch. Based on the analysis results, the R Square value is 0.174 or 17.4%. This shows that the compensation variable, motivation, is able to explain the work performance variable by 17.4%, while the rest is explained by other variables not included in this study. Kata Kunci/Keywords: Compensation; Motivation; Employee performance